(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Bondurant is of the opinion that the generic name ’Satyagraha’ is used to explain away almost any direct social or political action short of organised violence. Is Satyagraha to be equated with demonstration, shouting of slogans, fasting and boycott? Is it a constructive philosophy of action, a way of conducting conflicts when they arise, or merely a theoretical system of end structure aimed at ultimately eliminating conflict? There are always a set of characteristics which clearly differentiate one type of action from others. In this research paper, Properties peculiar to Satyagraha is described and on the basis of an understanding of these fundamental principles. It will also be mentioned that which techniques constitute Satyagraha, and which lead to the adoption of outward forms that superficially resemble the Gandhian to technique but are really scarcely different from traditional methods of strikes and demonstrations.